Acceptance of matchmaking tools in coworking spaces: an extended perspective - Cristopher Siegfried Kopplin; Till Marius Gantert; Julia Verena Maier (Review of Managerial Science, 2021)
An extended technology acceptance model for matchmaking tools in coworking spaces is presented and tested among 92 German coworkers. Advancing previous research, hedonic and community-related aspects are integrated into a framework based on the extended unified theory of acceptance and use of technology (UTAUT2). Coworkers emphasize a matchmaking tool's productivity aspects, which are positively moderated by their sense of community. Hedonic motivation (HM) and personal innovativeness contribute to usage intention, while effort expectancy is not a driver. The influence of HM is negatively moderated by sense of community, suggesting that a favorable social atmosphere that is explorable in person acts as a partial substitute for the enjoyment of tool usage. Surprisingly, satisfaction with face-to-face activities does not affect their perception of a matchmaking tool.
Keywords: M13; M19; O30; L26; 650; Coworking spaces; Matchmaking tools; Sense of community; Technology acceptance; Partial least squares; Structural equation modeling